(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2014)
Sesame (Sesamum indicum L.) is an annual herb not extensively cultivated in Bangladesh. The jute hairy caterpillar, Spilarctia (=Spilosoma) obliqua (Walker) was found to attack the foliages including tender shoots of sesame in the Oilseeds Cultivation Centre of BCSIR Laboratory Campus, Rajshahi. The other pests encountered were pentatomid bugs, Dolycoris indicus (Stal) and Nezara viridula (L.),a chrysomelid beetle, Aphthona nigrilabris (Duvivier), leaf sucking coleopteran beetle and Monolepta signata (Oliv.) The insect pests encountered in the Oilseeds Cultivation Centre, Patgram, Lalmonirhat were: a pyrrhocorid bug, Dysdercus koenigii Fab. and a pentatomid bug, Piezodorus hyubneri Gmelin (Fab.). The efficacy of five plant extracts or botanicals e.g., Bara Bishkatali (Polygonum orientale L.) leaf, custard apple (Annona squamosa L.) leaf, castor (Ricinus communis L.) seed oil and sesame oil (Sesamum indicum), a mixture of Neem (Azadirachta indica L.) seed oil and sesame oil have been evaluated for their pesticide action in the suppression of dominant insect pests of sesame. The treatment of custard apple leaf extract produced significant result in pest control and crop yield next to sesame oil. Other treatments also exhibited better results in comparison to the control. The yields were 858 and 642 kg per acre in the crop fields of Lalmonirhat and Rajshahi districts respectively. DOI: http://dx.doi.org/10.3329/bjsir.v49i1.18851 Bangladesh J. Sci. Ind. Res. 49(1), 31-34, 2014